PENGARUH TERMINOLOGI OLAHRAGA TERHADAP PENGEMBANGAN TEKNIK DAN TAKTIK: PERSPEKTIF PELATIH DAN AHLI OLAHRAGA DALAM MENINGKATKAN KINERJA ATLET - Fauzen, M. Nur Ridwan; Valentino Hary; Akbar Rohmad Aulia (Fakultas Pertanian, 2025)
This study aims to explore the influence of sports terminology on the development of techniques and tactics from the perspectives of coaches and sports experts in enhancing athlete performance. Using a qualitative method, data were collected through in-depth interviews with coaches and sports experts from various sports disciplines. The findings indicate that the use of appropriate terminology plays a crucial role in enhancing communication, strategic understanding, and team collaboration. Furthermore, the research reveals that clear and consistent terminology not only accelerates the learning process but also aids athletes in effectively applying techniques. Practical recommendations for coaches are proposed, including systematic teaching and the use of visualization to improve athletes' understanding. These findings are expected to contribute to the development of more effective and targeted training programs.